Translation, validation and cross-cultural adaptation of the Malay Emotion Regulation Checklist (ERC-M): a preliminary study - Jamal, Fatin Nabilah; Dzulkarnain, Ahmad Aidil Arafat; Shahrudin, Fatin Amira; Musa, Ramli; Sidek, Shahrul Na'im; Md Yusof, Hazlina; Khalid, Madihah (Malaysia Medical Association, 2021)
Objective: ERC has been used globally and translated to several languages, including Brazilian Portuguese, Italian and Persian. This study aims to translate and validate ERC to the Malay language and to measure the reliability and validity of the translated version of this scale among Malaysian parents. Methods: This study involved forward-back translation method. The translated questionnaire was then pretested and piloted among 10 parents and 50 participants, respectively. The procedure was repeated using the same questionnaire to evaluate the test-retest reliability. Results: The ERC-M has excellent qualitative and quantitative measurements in both I-CVI and S-CVI. In addition, the ERC-M demonstrated good internal consistency from Cronbach’s alpha and test-retest reliability based on the ICC in all domains. Conclusion: ERC-M potentially can be used as a tool to evaluate emotion for the population with emotional dysregulation issue, such as autism spectrum disorder.